Construção de um índice de fragilidade baseado na perda de solo e balanço hídrico climatológico - Santos, Fernanda Dias dos (2018)
The environmental planning of watersheds is an important instrument for the management of water resources. In order to contribute to the debate, some assumptions are presented for the environmental planning of river basins. The objective of this research was to test methodologies for determination of soil potential loss by erosion and climatological water balance to create subsidies for decision making for the environmental planning of the Cachoeira Cinco Veados Basin, RS. To estimate the potential loss of soil by erosion, the Universal Soil Loss Equation (USLE) was used to diagnose areas more susceptible to soil loss. To determine the climatological water balance, he used the BHCGeo.py script (CARVALHO NETO, 2011). For both, a Geographic Information System, the ArcGIS 10.5 software was used, where soil, rainfall, relief, land use, conservation practices and temperature factors were spatialized for the entire drainage area of the basin. The study area is located in the Ibicuí River Basin, at the geographical coordinates 29 ° 00 'and 29 ° 30' south latitude and 53 ° 39 'and 54 ° 06' west longitude and with a drainage area of 1541, 9 km2. It is inserted in the zone of transition between Central Depression and the Plateau Sul-Riograndense characterized by shallow to very deep soils, predominantly Neossolo U.M. Guassupi (48.9%), with flat relief to mountainous fort, being drained by the Toropi and Guassupi River, covering the municipalities of Tupanciretã, Quevedos, Júlio de Castilhos and São Martinho da Serra. Soil losses were calculated for the current land use situation of the basin, as well as for three scenarios elaborated according to land use and coverage: the entire area covered by rural use, the entire area covered by agricultural and livestock use and the whole area. area covered by forest / reforestation, and in both scenarios urban anthropic use areas are unchanged. For the climatological water balance the average temperature for the basin was considered, the available water capacity, according to the type and use of the soil and the average precipitation. Subsequently, the data were crossed, generating fragility maps for the basin, object of study. For potential soil loss, the highest values were found for the rural use scenario (3,211.49 ton.ha-1.year-1), followed by forest / reforestation use (1,267.54 ton.ha-1.year-1), current use (1,246.39 ton.ha-1.year-1) and agricultural use (600.82 ton.ha-1.year-1), where maximum rains were considered (rainy years). For the climatological water balance, the spatiality of the rains was verified throughout the year, and the temperature directly influences the balance through potential evapotranspiration. It was considered the average rains (normal years), minimum rains (dry years) and maximum rains (rainy years). The climatic water balance had the following variations: minimum: from -2 to 122 mm; average: from 2 to 144 mm and maximum from 15 to 167 mm, with the minimum and maximum values observed in January and October, respectively. In order to work on the environmental planning of the basin, the potential soil losses were divided into 7 classes (0 - 1, 1 - 10, 10 - 50, 50 - 100, 100 - 500, 500 - 1000 and 1000 - 5,000 ton.ha-1.ano-1) and the climatic water balance in 3 classes (<0; 0 - 5 and> 5 mm), considering minimum, medium and maximum rains, thus generating the fragility classes. The most fragile classes are found in the largest classes of soil loss and in the lowest classes of the climatological water balance, and, as rainfall increases, areas of criticality decrease, evidencing the fact that the region is more water deficit to water erosion. The environmental planning is necessary in the Cachoeira Cinco Veados Basin, RS, since even in scenarios, 15.81 km² are not yet usable because they present losses above the established limit.